The Correlation Between Listening Habit to English Song and Vocabulary Mastery - Wardiansyah .; Barnabas S.; Elfrida . (Journal of English Education and Teaching, 2019)
ABSTRACTThe aims of this research were to find out the correlation between students’ listening habit to English song and their vocabulary mastery. This research applied correlational study which was used quantitative design. The subjects were 60 students of Third Grade Students of SMPN 06 Kota Bengkulu. The data were collected from two instruments: (1) questionnaire was used to get data about students’ listening habit to English song and (2) VLT test was used to get data about students’ vocabulary mastery. The result of calculation was using Pearson Product moment formula process by SPSS IBM Statistic Version 20 Program, which showed the score of  rxy bigger than the score of r table (0,835 > 0,254). It means that Ha was accepted and H0 was rejected. In conclusions, there is a positive and significant correlation between listening habit to English song and vocabulary mastery of third grade students of SMPN 06 Kota Bengkulu.